(3GdLGeY GdUZjQ aj GdaQhYs - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEf eMeO Hf GdMSf QMeg Gddg hVY cJGHkG ai Gdabg hSeGg GdLGeY GdUZjQ hbO LeY ajg CQHYjf cJGHkG ef cJH Gdabg cJGH GdUdGI HGH eG jfbV GdhVhA s
(3BNQgG (B:s
(3eSGFd eJaQbI djSJ dgG CHhGH bGd dQLd dJcaQf HGddg Ch dCbJdfc aEfg jSYg Pdc hjDNP Cgd GdPeI HEXgGQ GdcSJjLGJ hGdQchH Ydi GdSQhL GdJi cgjFI GdCca hGdLgGO hGLH EdG Cf GdeSdejf ai YPQ MJi jMJGL Edjge hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3fSNI eUhQI Yf WHYI GdgfO GdMLQjIs
(3HChdg agQSJ ddcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs